2013
DOI: 10.1172/jci65636
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes induced by adenosine augmentation therapy prevent epileptogenesis

Abstract: Epigenetic modifications, including changes in DNA methylation, lead to altered gene expression and thus may underlie epileptogenesis via induction of permanent changes in neuronal excitability. Therapies that could inhibit or reverse these changes may be highly effective in halting disease progression. Here we identify an epigenetic function of the brain's endogenous anticonvulsant adenosine, showing that this compound induces hypomethylation of DNA via biochemical interference with the transmethylation pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
300
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(312 citation statements)
references
References 47 publications
11
300
0
1
Order By: Relevance
“…[20][21][22][23] More recent mouse studies showed that increased intracellular adenosine, resulting from genetic deletion of adenosine kinase, reverses elevated global DNA hypermethylation in specific neuronal cells of mouse models of epileptic disease. 24 Although early human studies showed that adenosine levels are increased in maternal and fetal circulation and placentas of patients with preeclampsia and that increased placental adenosine causes preeclampsia features in pregnant mice, 19,35,36 the possibility that elevated placental adenosine contributes to placental DNA hypomethylation associated with preeclampsia remained undetermined before our current studies. Here, taking advantage of our newly developed preeclampsia animal models genetically engineered to allow adenosine to accumulate in the mouse placentas, 19 we demonstrated that genetic deletion of placental ADA leads to increased placental adenosine, placental DNA hypomethylation, and preeclampsia symptoms in pregnant mice.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[20][21][22][23] More recent mouse studies showed that increased intracellular adenosine, resulting from genetic deletion of adenosine kinase, reverses elevated global DNA hypermethylation in specific neuronal cells of mouse models of epileptic disease. 24 Although early human studies showed that adenosine levels are increased in maternal and fetal circulation and placentas of patients with preeclampsia and that increased placental adenosine causes preeclampsia features in pregnant mice, 19,35,36 the possibility that elevated placental adenosine contributes to placental DNA hypomethylation associated with preeclampsia remained undetermined before our current studies. Here, taking advantage of our newly developed preeclampsia animal models genetically engineered to allow adenosine to accumulate in the mouse placentas, 19 we demonstrated that genetic deletion of placental ADA leads to increased placental adenosine, placental DNA hypomethylation, and preeclampsia symptoms in pregnant mice.…”
Section: Discussionmentioning
confidence: 80%
“…For this reason, elevated adenosine is associated with DNA hypomethylation. [20][21][22][23][24] However, the function of elevated placental adenosine in DNA hypomethylation in preeclampsia remains unknown largely because of the lack of in vivo experimental models. Here, we report the use of 2 independent preeclampsia models, both characterized by elevated placental adenosine 19 that led us to discover that elevated placental adenosine contributes to the placental DNA hypomethylation in preeclampsia.…”
Section: Hypertensionmentioning
confidence: 99%
“…The acute or initiating phase (lasting 2-3 h) is characterized by an acute surge in adenosine associated with a transient downregulation of astrocytic adenosine kinase (ADK), which commands the cellular uptake of the nucleoside from the extracellular milieu. Besides controlling neuronal excitability, high levels of adenosine can transiently reduce epigenetic DNA methylation, which precipitates epileptogenesis by favoring the transcription and expression of initiating genes [57]. In humans, the following weeks or months are critical for epileptogenesis as inflammatory processes are activated leading to microglial and astroglial activation (reviewed in [58,59]).…”
Section: Discussionmentioning
confidence: 99%
“…including epigenetic DNA methylation. ADK inhibitors and deficiency of ADK were shown to induce hypomethylation of DNA via biochemical interference with the transmethylation pathway in mice (Williams-Karnesky et al 2013). As may be expected from the importance of this pathway, autosomal-recessive ADK deficiency comprises a complex inborn error of metabolism with a severe clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%